Measurement of 10B concentration through autoradiography images in polycarbonate nuclear track detectors - Portu, Agustina Mariana (2011)
The determination of the local concentration of boron in the different regions of tissue samples treated by Boron Neutron Capture Therapy (BNCT) could be made through the evaluation of the number of tracks forming autoradiography images. It is necessary to get a "standard" material containing a known amount of 10B, to correlate the number of tracks and boron concentration, i.e. to be used as a reference. Different systems were tested in order to find a suitable standard. Films made of 2% agarose in boron solutions showed a homogeneous distribution of the 10B atoms in the material structure. This system is easy handled and its physical properties are satisfactory. On the other hand, a small volume polycarbonate box was designed to contain 10B solutions of known concentration. This system showed a reduced number of background tracks and a promising behavior in many aspects. There is proportionality between track numbers per surface unit and 10B concentration, and between track numbers per surface unit and neutron fluence. Experimental results were compared to calculated values through formulas developed for thick samples autoradiography.